Exploring adult vaccination awareness and practice: a cross-sectional study of knowledge, attitudes and immunization practices among postgraduates and interns at a tertiary care hospital - Nagaraju Vangapalli; Syed Mohsin Ahmed (International Journal of Basic & Clinical Pharmacology, 2026)
Background: Adult vaccination is an important part of disease prevention, but it is often not given enough attention, especially in developing countries like India. Many effective vaccines are available for adults, such as those for influenza, hepatitis B, and HPV, yet awareness and use of these vaccines remain low. Healthcare professionals, including interns and postgraduate students, have a key role in promoting vaccination among the public. Studying their knowledge, attitude, and practice (KAP) toward adult vaccination helps to find existing gaps and improve future vaccination programs. Methods: Predesigned and validated questionnaires were given to post graduates and Interns of the hospital. The KAP questionnaire which include 22 questions, out of these 8 questions are regarding knowledge, 7 for attitude, 5 for practice and 2 questions regarding barriers/facilitators to vaccination. The questionnaire was distributed to the participants electronically via google forms with digital informed consent, and their responses were collected and analyzed, results were expressed in frequencies and percentages. Results: Among 106 participants, 56 (52.8%) were females and 50 (47.2%) were males. All were postgraduate trainees and interns. About 71.7% knew that a separate adult vaccination schedule exists. Most participants agreed that adult vaccination is important, and many (66.7%) strongly agreed. Most (94.3%) had received at least one adult vaccine such as COVID-19 or Hepatitis B, and 76.5% had recommended vaccines to patients. However, some barriers like lack of awareness, time limits, and unclear institutional guidelines were noted. Conclusions: Overall, the study found good knowledge and a positive attitude toward adult vaccination among postgraduates and interns. Yet, some gaps remain in practical implementation and patient guidance. More structured training sessions, awareness programs, and clear hospital policies can help improve adult vaccination practices among healthcare workers.